Agile management and long-term strategy in exploration: the 'lucky' discovery of the Sinclair Pollucite Deposit, Eastern Goldfields, Western Australia. Issue 5 (4th July 2021) - Batt, G. E.; Crook, D.; Brand, N.; Kerr, S.
Abstract: Behind the inevitable headlines describing the 'lucky discovery' of the Sinclair Pollucite Deposit by Pioneer Resources in a drilling campaign targeting lithium mineralisation, the identification, delineation and development of this resource present a deeper and more substantial tale of fundamental mineral exploration strategy and agile management. A window of opportunity provided by booming global interest in Li exploration delivered Pioneer the impetus and capital to leverage deep geological knowledge of the Pioneer District, innovative exploration technologies, and lean and agile management practices in the development and implementation of a successful exploration campaign targeting the previously unappreciated pegmatites of the Pioneer Dome. While not the target of the original drilling, the intersection of high-grade pollucite at Sinclair was fully consistent with the mineral systems model underlying Pioneer's exploration plan. By pursuing a flexible process-based targeting approach and retaining the capacity to pivot the focus of their exploration team onto this find, Pioneer were able to rapidly define and exploit the pollucite resource at Sinclair, despite the absence of national precedent. KEY POINTS: The Sinclair pollucite resource is without precedent in Australia. Discovery of this deposit followed from consistent long-term investment in district mineral exploration. Responsiveness and rapid decision-making were critical to the successful development of this unexpected discovery.